2020
DOI: 10.3390/insects11010063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Metaphase Chromosome Karyotypes in Imaginal Discs of Aedes communis, Ae. punctor, Ae. intrudens, and Ae. rossicus (Diptera: Culicidae) Mosquitoes

Abstract: In this study, cytogenetic analysis of the metaphase chromosomes from imaginal discs of Aedes (Diptera: Culicidae) mosquitoes—Aedes communis, Ae. punctor, Ae. intrudens, and Ae. rossicus—was performed. The patterns of C-banding and DAPI staining of the heteroсhromatin and the length of the chromosomes demonstrate species specificity. In particular, the Ae. punctor chromosomes are the shortest compared with Ae. communis, Ae. intrudens, and Ae. rossicus, and they also carry additional C and DAPI bands in interca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…behningi and Ae. punctor has shown that the all three pairs of chromosomes in the examined species are metacentric [6,7].…”
Section: видовая специфика распределения гетерохроматинового блока и mentioning
confidence: 87%
“…behningi and Ae. punctor has shown that the all three pairs of chromosomes in the examined species are metacentric [6,7].…”
Section: видовая специфика распределения гетерохроматинового блока и mentioning
confidence: 87%
“…The previous studies on genome size evaluated the phylogenetic relations in the taxonomy field [6,7,8] ; estimated the completeness of genomes [9] ; and helped in assessing genetic linkage maps [10] . Genome size was usually considered constant within species, and could vary widely between closely related species [27] .…”
Section: Main Bodymentioning
confidence: 99%
“…Karyotype analysis can serve as an additional tool in the species level identification of the species, which have morphological similarity and require additional identification methods. Using morphological, molecular, and karyotypic data, more precise species identification can be performed (Alekseeva et al 2020).…”
Section: Introductionmentioning
confidence: 99%